BILLING IS A DEVELOPING MEANS OF BRANDS PROMOTION - Vladimir A. Polyakov; Andrey A. Romanov (Статистика и экономика, 2016)
The article gives a concept of the billing as a developing means of marketing promotion. Examples of comparative analysis for a rating are considered. The author presents technology of two-factor rating of trade marks on the basis of expert and comparative analysis.